Internal Self-determination and the Prevention of Secession in International Law - Janković, Sava, (Developments in International Law ;, 2025)
Internal self-determination (ISD) empowers communities to shape their destiny within a state, transforming tension into opportunity. By actively engaging citizens in decision-making, governments can tailor policies to meet unique cultural and economic needs, quelling discontent and building trust. This dynamic process channels energy into reform and inclusion, ensuring every voice is heard and valued. As grievances are addressed, loyalty to the state strengthens and the appeal of secession fades. Ultimately, internal self-determination fosters unity, invigorates national pride, and creates a resilient, inclusive society that prevents fragmentation and secures lasting peace. Recognizing that self-determination extends beyond its traditional external form to include internal practices offers a viable solution for preserving its contemporary legal relevance and advancing human rights.